Vetenskaplig expertis och Nordområdets naturresurser - Wråkberg, Urban (Nordlit, 2012)
The essay reflects on political pressures exerted by and on scientists and technologists acting as advisors on political and economic matters of the high north.It uses two case studies to do this. One consists in the group of scientists from several nations who engaged as advisors to their foreign offices in the process leading up tothe ratification of the Spitsbergen/Svalbard treaty in 1920. The focus is on the discourse regarding hunting, mining and nature protections on these islands. The second case is the way technologists and geological scientists were engaged in the industrialisation of the USSR. These contexts of course differ in scale and in many other ways but are similar in certain respects. The discussion is centred on the problems of technocracy which is commented based on the Frankfurt school's elaborations on the open society and differing interpretations of technological determinism. This is related further to contemporary contentions over the balance between scientific based environmental stewardship and technological management in northern raw material extraction.